2000
DOI: 10.1016/s0029-7844(99)00664-x
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic fluid soluble fas levels in intra-amniotic infection

Abstract: Elevated AF sFas is associated with intra-amniotic infection. High production of AF sFas in intra-amniotic infection may play a role in the inhibition of apoptosis of AF leukocytes, leading to the persistence of inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…However, soluble Fas, an alternatively spliced product of the Fas gene, protects the target cells from Fas-mediated apoptosis by neutralizing binding between membrane-bound Fas and the Fas ligand [ 126 ]. It has been proven that the concentration of soluble Fas in the amniotic fluid is high [ 127 ]. In addition, Fas has been shown to be expressed predominantly in epithelial cells throughout the whole amnion, so it is reasonable to hypothesize that hAESCs are one of the major sources of soluble Fas existing in the amniotic fluid [ 128 ].…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…However, soluble Fas, an alternatively spliced product of the Fas gene, protects the target cells from Fas-mediated apoptosis by neutralizing binding between membrane-bound Fas and the Fas ligand [ 126 ]. It has been proven that the concentration of soluble Fas in the amniotic fluid is high [ 127 ]. In addition, Fas has been shown to be expressed predominantly in epithelial cells throughout the whole amnion, so it is reasonable to hypothesize that hAESCs are one of the major sources of soluble Fas existing in the amniotic fluid [ 128 ].…”
Section: The Paracrine Effect Of Human Amniotic Epithelial Stem Cementioning
confidence: 99%
“…Kubo et al transplanted human amnion to both the rat limbal area and under the kidney capsule and found that the xenogeneic (human to rat) immune responses were significantly mitigated [15]. In addition, all HLA-G, CD59, and FasL are secreted from hAECs into amniotic fluid [16,17]. These soluble factors provide immune tolerance not only to the transplanted hAECs but also to neighboring cells.…”
Section: Immune Privilegementioning
confidence: 99%
“…51,52 A previous report showed that soluble Fas (sFas) is elevated in the AF of patients with MIAC complicated by PTL or PPROM. 53 Balkundi et al also reported that increased trophoblast Fas expression and apoptosis are associated with severe acute HCA (grade 3). 54 Similar to these results, Annells et al reported that polymorphisms in FAS gene promoter are negatively associated with acute HCA in women with preterm birth.…”
Section: Discussionmentioning
confidence: 97%
“…Noteworthily, both Fas and Fas ligands are expressed in the human placenta and fetal membranes (amnion, chorion, and chorioamnion) during gestation 51,52 . A previous report showed that soluble Fas (sFas) is elevated in the AF of patients with MIAC complicated by PTL or PPROM 53 . Balkundi et al.…”
Section: Discussionmentioning
confidence: 99%